Analisis Tingkat Keterampilan Servis Atas Pemain Bolavoli Sma Negeri 10 Kota Bengkulu - Ferdian, Muhammad Alfan; Apriansyah, Dolly; Sumantri, Ajis (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the level of upper service skills of volleyball players of SMA Negari 10 Bengkulu City. This type of research is descriptive quantitative using survey methods and data collection techniques using tests and measurements. The results of this study based on the volleyball game top service skills test it is known that the category is very poor 0% (0 players), the category is less by 6.7% (1 player), the moderate category is 60% (9 players), the good category is 26.7% (4 players), and the excellent category is 6.7% (1 person). Based on the results above, it can be concluded that the upper service skills of SMPA 10 volleyball players in Bengkulu City are in the MEDIUM category, namely 9 players or with a percentage of 60%.